Analisis Kebutuhan LKPD Elektronik Bernuansa Emotional Spritual Quotient pada Materi Keanekaragaman Hayati: E-LKPD, Emotional Spiritual Quotient (ESQ), Keanekaragaman Hayati - jelly kumala sari, jelly; Lufri, Lufri (Al-Alam: Islamic Natural Science Education Journal, 2025)
Learning media is a tool that has a crucial role in supporting the teaching and learning process, because media functions as a means of conveying effective information to students. One of the teaching media that is widely used is student worksheets. With advances in technology, electronic-based student worksheets are needed. Electronic LKPD is a student practice sheet that is done digitally and carried out systematically. This research aims to identify students’ needs for e-LKPD that integrates Emotional Spiritual Quotient (ESQ) aspects as additional teaching materials in learning activities. This research uses descriptive methods with quantitative and qualitative approaches. Data collection techniques were through interviews with a biology teacher and distributing questionnaires to 70 students in Classes X E1 and X E2 at SMAN 1 Koto XI Tarusan. The interview results showed that the teacher only used the textbook provided by the school and had never developed e-LKPD with Emotional Spiritual Quotient (ESQ) nuances in learning activities. So students do not have supporting teaching materials to be able to learn independently. From this research it can be concluded that there is a great need for e-LKPD with Emotional Spiritual Quotient (ESQ) nuances regarding biodiversity material.